Prior stress and vasopressin promote corticotropin-releasing factor inhibition of serotonin release in the central nucleus of the amygdala - Ronan, Patrick J.; Korzan, Wayne J.; Johnson, Philip L.; Lowry, Christopher A.; Renner, Kenneth J.; Summers, Cliff H. (Frontiers in Behavioral Neuroscience, 2023)
Corticotropin-releasing factor (CRF) plays a significant role coordinating endocrine and neural responses to stress, frequently facilitated by vasopressin (AVP). Previous work has linked CRF hypersecretion or binding site changes and dysfunctional serotonergic transmission with anxiety and affective disorders, including clinical depression. Additionally, CRF has been shown to alter serotonergic activity. In the dorsal raphé nucleus and serotonin (5-HT) terminal regions, CRF effects can be stimulatory or inhibitory, depending on dose, site and receptor type activated. Prior stress alters CRF neurotransmission and CRF-mediated behaviors. Lateral, medial, and ventral subdivisions of the central nucleus of the amygdala (CeA) produce CRF, and coordinate stress responsiveness. The purpose of these experiments was to determine the effect of intracerebroventricular (icv) administration of CRF and/or AVP on extracellular 5-HT as an index of 5-HT release in the CeA, using in vivo microdialysis in freely moving rats and high performance liquid chromatography (HPLC) analysis and to examine the effect of prior stress (1 h restraint, 24 h prior) on CRF- and/or AVP-mediated release of 5-HT within the CeA. Infusion (icv) of CRF into the CeA of unstressed animals had no effect on 5-HT release in the CeA. In contrast, in rats that received prior stress, CRF caused a profound dose-dependent decrease in 5-HT release within the CeA. This effect was long-lasting (240 min); and was mimicked by CRF plus AVP infusion without stress. Thus, prior stress and AVP functionally alter CRF-mediated neurotransmission, sensitizing CRF-induced inhibition of 5-HT release; potentially a mechanism underlying stress-induced affective reactivity in humans.